Work-related disease symptoms and occupational injuries among coffee processing industry workers in Bench-Sheko and Kaffa Zones Southwest, Ethiopia: A mixed-method study - Mekonnen, Besufekad; Solomon, Nahom; Wondimu, Wondimagegn; Tesfaye, Melkamsew; Negash, Samuel (Frontiers in Public Health, 2022)
Background:- Occupational injuries have become one of the most essential rooting factors contributing to disabilities and life-threatening situations in developed and developing countries. Workers in the coffee industry face some occupational health and safety issues. However, there is limited evidence on this important public health issue. Hence, this research was conducted to assess work-related disease symptoms and occupational injuries among coffee processing workers in Southwest, Ethiopia. Methods: A cross-sectional study supplemented with qualitative research was conducted. A total of 721 workers were included in the study for quantitative information and a total of 22 in-depth interviews and 5 key informant interviews were conducted for generating qualitative evidence. Quantitative data was collected by an interview-based questionnaire which is adapted from similar studies. Descriptive statistics, binary logistic, and multivariable logistic regression analysis were done to identify the factors affecting occupational injuries. Qualitative data were collected through interviews using an interview guide and collected data were transcribed verbatim and analyzed with ATLAS ti version-8 by applying a content analysis approach. Result: - The overall prevalence rate of work-related symptoms and occupational injuries among coffee processing workers were 21.7% and 13.4% respectively. Age group 30-39 and 40-49 (Adjusted odds ratio (AOR) 1.95, 95% CI 1.37, 2.79, (AOR 3.28, 95% CI 1.89, 5.69, respectively, income level (AOR 0.24, 95% CI 0.16, 0.36, p = 0.000), experience (AOR 1.64, 95% CI 1.04, 2.60, p=0.034), and smoking cigarette (AOR 5.59, 95% CI 2.78, 11.26, p=0.000) were significantly associated with work-related symptom. In addition, training related to the job (AOR 11.88, 95% CI1.34, 105.57, p=0.026) was significantly associated with occupational injuries among coffee processing industry workers. Conclusion: - The prevalence of work-related symptoms and occupational injuries was high among coffee processing industry workers of southwest Ethiopia. Therefore, there is a need for regulations at both government and industry owner levels to improve the working conditions and ergonomic structure of coffee processing industries.